Evaluation of sub-chronic chlorpyrifos poisoningon immunological and biochemical changes in ratsand protective effect of eugenol - Ibrahim A. Elelaimy, Hany M. Ibrahim, Faten R. Abdel Ghaffar, Yahia S. Alawthan (Journal of Applied Pharmaceutical Science)
Chlorpyrifos (CPF) is one of the most widely used organophosphorus (OP) insecticides until 2000 when the United States Environmental Protection Agency restricted some of its domestic uses due to its toxicity. Despite this, CPF remains one of the most widely used OP insecticides. Eugenol is a flavoring agent used in cosmetic and food products. Furthermore, eugenol acts as a pro-oxidant and as an anti-oxidant, under certain circumstances. Therefore, the present study aims to evaluate the possible immuno-toxicogical consequences produced by CPF on different immunological aspects and to assess the protective role of eugenol in attenuating the CPF-induced immunotoxicity. The changes in humoral and cell mediated-immunity were evaluated by measuring the level of immunoglobulin (IgG), lymphocyte viability, neutrophil phagocytic function assay, total white blood cells count (WBC) and relative differential white blood cells count. On the biochemical level, estimation of nitric oxide (NO) level and catalase activity was also undertaken. The treatment with CPF showed an inhibitory effect on the level of lymphocyte viability, neutrophil phagocytic index, total white blood cells count, relative lymphocyte count, IgG concentration and catalase activity. On the other hand, a high level of NO was detected upon animal treatment with CPF. Interestingly, eugenol pre- and post-treatment to CPF-treated group improved the lymphocyte viability, total white blood cells count, relative lymphocyte count, catalase activity and the NO level. Moreover, eugenol pre- and post-treatment recovered phagocytic activity of neutrophils and restored IgG level. In conclusion, eugenol has protective and curative roles in attenuating the CPF-induced immunotoxicity.
Keywords: chlorpyrifos,eugenol,lymphocyte,phagocytosis,IgG.